(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2022)
The present study aimed to characterize the primary vegetation of the Pedro Franco Dávila tropical moist forest in the province of Los Ríos, Ecuador. Two permanent plots of 50 x 50 m2 were randomly established in the study area at a distance of 100 m each other. The species in each plot were identified and dasometric data such as diameter at breast height (DBH), from 10 cm and total height (Ht) were meassured to calculate the basal area and volume of all the individuals registered. A total of 155 arboreal individuals distributed in 12 families, 19 genera, and 19 species were recorded. The floristic composition of the Pedro Franco Dávila primary humid forest is characterized by the Moraceae, Fabaceae, and Rubiaceae families. At the species level, it is characterized by the presence of two species of mature forest Castilla elastica, Erythrina poeppigiana and two small trees of mature forest such as: Duguetia peruviana and Stenostomum acreanum, these species representing 55.4% of all individuals recorded in 5000 m2. At structural level, the forest is determined by a greater presence of arboreal individuals in smaller diameter classes between 10-19 cm with 59.35% and lower height classes between 10-19 m with 57.41%. These are decreasing in quantity while the DBH increases, exhibiting the characteristic inverted J-shaped curve. The Shannon index shows medium dominance, that is, there are no dominant trees, due to the decrease in emerging individuals from primary forest.